High-fat diet impact on prostate gland from adiponectin knockout mice: Morphometric, metabolic and inflammatory cytokines analyses - Gabriel, Ana Luiza R. [UNESP]; Mosele, Francielle C. [UNESP]; Fioretto, Matheus Naia [UNESP]; Oliveira, Beatriz S. [UNESP]; Felisbino, Sergio Luis [UNESP] (Elsevier, 2024)
Aims: Obesity is a global public health issue, and some studies have linked it to an increased risk of prostatic diseases. This study aimed to evaluate the effects of a high-fat diet on metabolic parameters and prostate morphology in wild-type (WT) and adiponectin knockout (KO) mice. Main methods: Male WT and KO mice were fed a control diet (CD) or high-fat diet (HFD) for 6 months. Serum metabolic parameters, inflammatory cytokines in epididymal fat tissue, dorsal prostatic lobe morphometry and histopathology were analyzed. Key findings: CD WT and CD KO mice did not exhibit altered metabolic or prostatic parameters. However, HFD WT mice showed altered glucose and insulin tolerance even without excessive weight gain. On the other hand, HFD KO mice developed obesity, with an increase in low-density lipoprotein (11.8 ± 5.1 vs. 31.4 ± 3.6 mg/dL), high-density lipoprotein (73.4 ± 7.4 vs. 103.4 ± 2.5 mg/dL), and total cholesterol levels (126.2 ± 16.1 vs. 294.6 ± 23.2 mg/dL), a decrease in insulin levels (28.7 ± 12.2 vs. 4.6 ± 2.3 μIU/mL), and glucose and insulin resistance. We also observed that HFD KO animals display an increase in inflammatory cytokines, such as IL6, IL1β, and IL1RA. The dorsal prostate from HFD KO animals also presented significant increases in the mast cells (1.9 ± 0,7 vs. 5,3 ± 1.5 cells/field) and Ki67 index (2.91 ± 0.6 vs. 4.7 ± 0.4 %). Significance: The above findings highlight the complex interactions between adiponectin, metabolism, malnutrition, and prostate health. Metabolic deregulation combined with adipose inflammation potentially induces a proliferative and inflammatory microenvironment in the prostate gland under conditions of low adiponectin production, potentially impairing prostate morphophysiology in the context of obesity and aging.
Keywords: Adipokine; Dorsolateral prostate; Inflammation; Mast cell; Obesity